Learning Menstrual Treatise Law to Answer Problematics about Haid on Students - Ferry Irawan Febriansyah; Estiti Rifngatul Kamila (Tarbiyah Departement collaboration with AMCA, 2020)
Probelamtika faced by adolescents today is very complex. The problems faced are mainly young women whose ages have reached adulthood with the mark being menstruating. This is often a problem due to ignorance and lack of learning about menstruation treatises for teenagers, especially women. This paper memcona provide legal information related to the learning of menstrual treatises in dealing with problems in students. This research focuses on qualitative research that uses data from observations, interviews and documentation to find the results of the research as outlined descriptively. The results of the application of menstrual treatise law learning conducted by teachers must perform a variety of strategies and methods that are good because it sees from the condition of students from different environments, so it is expected that a teacher in the implementation of menstrual treatise law learning can choose how to overcome these differences. This application must have participation from both students and parents.